Pengaruh Penerapan Green Accounting terhadap Profitabilitas pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Nining Purwanti; Samirah Dunakhir; Azwar Anwar (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to analyze the effect of implementing green accounting on profitability in Basic Industry and Chemical Sector Companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population of this research is all Basic Industry and Chemical Sector Companies listed on the Indonesia Stock Exchange (BEI) totaling 70 companies with samples for three years from 2020-2022 totaling 22 companies with a period of 3 years so that we got 66 samples taken using the Purposive Technique Sampling. Data collection was carried out using documentation techniques. Data analysis was carried out with SPSS 23 using multiple linear regression tests, classical assumption tests, and hypothesis tests. Based on the results of partial testing (T test), the environmental cost variable has a significant effect on profitability, indicating that environmental costs can have a large effect on the company's ability to earn profits. Meanwhile, the environmental performance variable does not have a significant effect on profitability, which shows that whether a company's environmental performance is good or bad does not affect the company's profit even though the company has a good PROPER rating. Based on the results of simultaneous testing (F test) environmental costs and environmental performance together have a simultaneous effect on profitability